2019
DOI: 10.3390/polym11091525
|View full text |Cite
|
Sign up to set email alerts
|

Production of Novel Polygalacturonase from Bacillus paralicheniformis CBS32 and Application to Depolymerization of Ramie Fiber

Abstract: Polygalacturonase (EC. 3.2.1.15) is an enzyme that hydrolyzes the alpha-1,4 glycosidic bonds between galacturonic acid. In this study, an alkaline polygalacturonase producer Bacillus paralicheniformis CBS32 was isolated from kimchi (conventional Korean fermented food). The 16S rRNA sequence analysis of the isolated strain revealed that it was 99.92% identical to B. paralicheniformis KJ 16LBMN01000156. The polygalacturonase from B. paralicheniformis CBS32 was named PN32, and the purified PN32 showed a 16.8% yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Denaturation of the enzyme was due to the release of covalent and hydrogen bond in the structure of the enzyme protein. The liberation of these bonds results in the disintegration of the enzyme protein folds that caused enzyme inactivation (Reece et al, 2011) The optimum PG activity was observed with NaCl followed by CaCl2 in BR3 isolate the opposite of what is in isolate BR5 and There was no obvious difference was observed in PG activity when using NaCl and CaCl2 in BR2 isolate, while the inhibited of PG activity was observed with CO 2+ and K + ions several studies (Manachini et al, 2005;Trindade et al, 2016;Rahman et al, 2019;Almulaiky et al, 2020) were clarified that the effect of various metal ions on the activity of PG enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denaturation of the enzyme was due to the release of covalent and hydrogen bond in the structure of the enzyme protein. The liberation of these bonds results in the disintegration of the enzyme protein folds that caused enzyme inactivation (Reece et al, 2011) The optimum PG activity was observed with NaCl followed by CaCl2 in BR3 isolate the opposite of what is in isolate BR5 and There was no obvious difference was observed in PG activity when using NaCl and CaCl2 in BR2 isolate, while the inhibited of PG activity was observed with CO 2+ and K + ions several studies (Manachini et al, 2005;Trindade et al, 2016;Rahman et al, 2019;Almulaiky et al, 2020) were clarified that the effect of various metal ions on the activity of PG enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…An endo-PG (EC 3.2.1.82), PehA (also known as PglA), cleaves the pectic polymer internally at random, releasing large oligomers, predominantly galacturonic acid (galUA) trimers (Allen et al, 1991;Roberts et al, 1988). Many investigators studied the effects of pH, temperature, incubation time, metals ions and Na concentration on the PG activity (Mathew et al, 2008;Maisuria et al, 2010;Anam and Latif., 2012;Martins et al, 2013;Rahman et al, 2019;Almulaiky et al, 2020;Berber and Çetinkaya, 2020). They assayed the enzyme activity at different pH, different temperatures, different incubation times, different metals ions and different NaCl concentrations under standard assay conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ample diversity of alpha-amylases with respect to the molecular weights (10 to 210 kDa) has been reported (Mehta and Satyanarayana, 2016). Raul et al (2014) reported molecular weight of α-amylase from Bacillus species ranges between 50 and 60kDa, while Rehman et al (2019) detected Polygalacturonase from Bacillus paralicheniformis to have molecular weight of 110 kDa. Hatice et al (2016) observed two protein bands belonging to pectinase of B. subtilis with molecular weights 60 and 64 kDa.…”
Section: Molecular Identification Of Selected Bacteriamentioning
confidence: 99%
“…This peel is a rich source of carbohydrates, flavonoids and oxidants. In general, pectinases, cellulases and amylases are involved in the degradation of pectin, cellulose and starch rich substrates (fruit peels) where bacteria play a crucial role in producing these enzymes (Ahlawat et al, 2009;Rehman et al, 2019;Dai et al, 2020). Citrus peel is reported to be one of the potential substrates for production of pectinase solely.…”
Section: Introductionmentioning
confidence: 99%
“…B. paralicheniformis were reported as plant-associated bacteria, displaying growth promoting abilities (Annapurna et al, 2018) and the potential to be used as phytopathogen biocontrol agents (Wang et al, 2017;Pylro et al, 2019;Jinal et al, 2020;Ramirez-Carino et al, 2020). B. paralicheniformis strains also have the potential to be used for biotechnological purposes and for bioremediation (Rahman et al, 2019;Khan et al, 2018;SanthaKalaikumari et al, 2021;Ganesh Kumar et al, 2021). Ahire et al (2020) reported the production of a bacitracin, an antimicrobial peptide active against a range of Gram-positive bacteria, by strains of B. paralicheniformis.…”
Section: Body Of Knowledgementioning
confidence: 99%